Pengaruh Harga Per Nilai Buku, Margin Laba Bersih Dan Rasio Pendapatan Harga Terhadap Kesulitan Keuangan Pada Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Johannes Kristian Siregar (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
A phenomenon that occurs in financial sector service industry companies in the banking sector listed on the Indonesia Stock Exchange for the 2015-2019 period where financial reports show the company's performance. The 2015-2019 period shows a fluctuating trend which can be seen from PBV, NPM, PER and Financial Distress, the level of difficulty in the financial sector, especially banking, has decreased in average profit by 30.23% in 2018, this is due to the high risk of accounts receivable. The purpose of this study is to determine how the effect of price per book value, net profit margin and price income ratio on financial distress in the financial sector listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The research method used is descriptive method. The sampling technique uses random sampling technique. This study uses descriptive and verification (quantitative) analysis techniques using path analysis. Data collection techniques are carried out by field studies and literature. The results showed that the price per book value, net profit margin and the ratio of price income to financial distress were obtained (1) PBV, NPM, PER partially had a significant positive effect on Financial Distress (2) Simultaneously had a significant positive effect against Financial Distress